FLEXIBLE BLENDED LEARNING EXPERIENCES OF FILIPINO STUDENTS IN AN ENGLISH AS A SECOND LANGUAGE (ESL) LEARNING CONTEX - Nikka Mae Jimenez Adling (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
The Coronavirus Disease 19 (COVID-19) outbreak has caused a sudden shift in many educational institutions to various alternative instructional methodologies. This pandemic has altered the traditional and typical strategies for teaching and learning environments. Marinduque State College (MSC), a Higher Education Institution (HEI) in the province of Marinduque, has implemented Flexible Blended Learning (FBL) for Academic Year (A.Y.) 2020–2021. This descriptive research determined the FBL experiences of MSC students in an English language-learning context. The study results revealed that MSC students have an overall positive experience with FBL implemented in their English language class. Nevertheless, continuous support to meet the needs of the most vulnerable students, who cannot entirely keep abreast of the new learning system, must be prioritized. This may help mitigate the widening inequality among students with their right to equal learning opportunities.